Symposium 4: Teacher Collaboration in the Context of Networked Learning: Current eTwinning Practices and Future Perspectives - Cachia, Romina; Punie, Yves (Proceedings of the International Conference on Networked Learning, 2012)
This article identifies emerging trends and challenges for teacher networking and collaboration in the context of networked learning based on a review of existing literature and on three consultation workshop with practitioners and stakeholders. In total, around 70 different people have been consulted to explore the potential of networks in the context of teacher collaboration. We argue that while the future of learning has been discussed extensively, the role of teachers, and more specific the role of teacher collaboration through networks is perhaps less taken into account. This article aims to demonstrate the importance of current and future networks for teacher collaboration and to highlight key issues to be taken into account for the further development of teacher networking, both as a practice and as an object of study. In general, teachers themselves are quite positive on the use and potential of ICT-enabled networks for improving the quality of their work, and they would like to see a more widespread use of ICT for collaboration with their peers, especially across borders and cultures. However, recognition of this work as part of their continuous professional development is regarded as important, as well as support and training to deal with data management, privacy and security issues. There is also a strong need for pedagogic training which empowers teachers with the required ICT skills to help their students become digitally competent and for guiding students towards more exploratory and creative interaction with ICT tools. It should be highlighted that already today; the eTwinning platform proves to be quite a significant activity for those teachers involved. Openness, flexibility and interoperability are regarded to be important for the future development of teacher collaboration networks.